EXHAUST EMISSIONS OF 4 STROKE SPARK IGNITION ENGINE WITH INDIRECT INJECTION SYSTEM USING GASOLINE-ETHANOL FUEL - Mega Nur Sasongko (Journal of Environmental Engineering and Sustainable Technology, 2017)
Gasohol can be replaced in the spark ignition engine (SI engine) as gasoline substitution having lower emissions exhaust gas, making it more environmentally friendly. The aim of study was to investigate the effect of gasoline- ethanol  ratio on the gas exhaust emission of SI engine injection system. In this study, it was used the 4-stroke gasoline engine injection system by using the injector as a fuel input device. The engine had a 124.8 cc single-cylinder engine with compression ratio of  9.3:1. The variations of gasohol were gasohol E0, E10, E20, E30, E40, E50, E60, E70, E80, E90 and E100 with range of speeds; 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm and 5000 rpm. The research was run by rearranging the standard ECU to obtain the AFR stoichiometric of each gasohol mixture. The exhaust emissions were measured by using the Stargas-898. The results show that the addition of ethanol content was able to increase the CO2 emissions , however, it would decrease the CO and HC levels. Compare to the gasoline fuel, gasohol has a lower emission of CO, HC and higher of  CO2 and O2 emissions.